CAPITALIZING YOUR TECHNOLOGY TO DISRUPT AND DOMINATE YOUR MARKETS transforming cost centers to innovation centers. - Ben-Yosef, Aviv (PRODUCTIVITY PRESS, 2023)
This book helps them bridge the culture gap between the C-suite and R&D, cover frequent tech-related decisions and issues, and provide a way to unlock tech as an offensive weapon and a strategic differentiator.